2011
DOI: 10.2174/156802611796117685
|View full text |Cite
|
Sign up to set email alerts
|

Role of Progesterone in Human Astrocytomas Growth

Abstract: Progesterone (P) participates in the regulation of several reproductive processes such as ovulation and sexual behavior, however, this hormone also participates in non-reproductive processes, such as neural excitability, learning and memory, and pathological processes such as cancer. P mainly elicits its effects by interaction with its intracellular receptor (PR), which is a ligand-activated transcription factor that modifies the expression of genes involved in the control of cell growth and proliferation, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 0 publications
2
19
0
Order By: Relevance
“…We also observed that RU486 blocked P 4 effects, since rats treated with P 4 + RU486 showed a significant decrease in tumor area in comparison with those treated with P 4 . These data are also consistent with previous reports in astrocytoma cell cultures [23, 26] and suggest that P 4 effects on astrocytoma cell growth occur via the classic mechanism of action, through an interaction with PR.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We also observed that RU486 blocked P 4 effects, since rats treated with P 4 + RU486 showed a significant decrease in tumor area in comparison with those treated with P 4 . These data are also consistent with previous reports in astrocytoma cell cultures [23, 26] and suggest that P 4 effects on astrocytoma cell growth occur via the classic mechanism of action, through an interaction with PR.…”
Section: Discussionsupporting
confidence: 93%
“…The increase in tumor growth after P 4 administration observed in our in vivo conditions is consistent with the results observed in in vitro experiments with U373 cells [23, 26]. Additionally, it has been reported that, in U373 cells, P 4 increases S-phase of the cell cycle [23] which could explain the increase in cell proliferation and therefore in tumor size.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is widely accepted that progesterone participates in the development of different types of cancer as a transcription factor [14,30,31]. It was reported [14,15] that progesterone-receptor isoforms are expressed in two cell lines (U373 and D54) derived from high-grade human astrocytoma. The same authors also demonstrated that progesterone increased VEGF and EGFR expression and cell proliferation, Mifepristone was able to inhibit not only the progesterone effects but also when it was administered alone significantly reduce astrocytoma cell growth in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The same authors also demonstrated that progesterone increased VEGF and EGFR expression, and cell proliferation in two human astrocytoma cell lines derived from tumors of different evolution grades (U373 grade III and D54 grade IV) and these effects were inhibited by Mifepristone [14,15]. Other authors have also showed that the expression of VEGF in prostate cancer cells DU 145 and PC3 treated with 10 micromol/L of Mifepristone was significantly decreased [16].…”
Section: Introductionmentioning
confidence: 98%